The Effect of Progressive Relaxation Exercises Administered via Telenursing on Sleep Quality of Nursing Students After the Earthquake in Turkey - Cevik Aktura, Seher; Özer, Gül Şevval (Lippincott Williams and Wilkins, 2026)
The study aims to examine the effect of progressive relaxation exercises administered to nursing students through telenursing on sleep quality after the February 6 earthquake in Turkey. The randomized controlled study included 86 nursing students from 2 universities in eastern Turkey, residing in one of the 11 cities affected by the February 6 earthquake. Experimental group received progressive relaxation exercises for 20 minutes every night for 4 weeks by making a video call with the student. Data were collected using a personal information form and the Pittsburgh Sleep Quality Scale. Although there was no significant difference between the pre-test PSQI mean scores of the experimental group and the control group (P>.05), a significant difference was observed between their post-test mean scores (P<.005). The research results showed that progressive relaxation exercises can be an effective intervention in improving sleep quality after an earthquake. In addition, conducting these exercises through telenursing contributed significantly to the sustainability and control of the intervention. Copyright © 2026 Wolters Kluwer Health, LLC. All rights reserved.
Keywords: Earthquake; Nursing Students; Progressive Relaxation Exercises; Sleep; Telenursing